The Role of the Ummul Ayman Islamic Boarding School in Samalanga District, Bireuen Regency in the Education of Children Victims of the Aceh Conflict, 1990-2021 - Sinthia Yuriza; Muhammad Haikal (Riwayat: Educational Journal of History and Humanities, 2022)
This study aims to find out how (1) the background of the birth of the Ummul Ayman Islamic Boarding School was, (2) the education management system of the Ummul Ayman Islamic Boarding School was in handling children victims of the Aceh conflict before the Helsinki MoU. (3) the education management system of the Ummul Ayman Islamic Boarding School in handling children victims of the Aceh conflict after the Helsinki MoU, (4) the results of the education process for children of Aceh conflict victims at the Ummul Ayman Islamic Boarding School were . The approach used in this research is a qualitative approach with data collection techniques in the form of interviews, documentation, and literature studies. The results of this study are (1) the background of the establishment of the Ummul Ayman Islamic Boarding School when conditions in Aceh were being hit by armed conflict which caused many negative impacts and the destruction of the social order of society in various aspects of life , especially in the aspect of education. (2), the education management system of the Ummul Ayman Islamic boarding school before the peace in Aceh followed the national education system, while the non-formal education system of the Ummul Ayman Islamic boarding school followed the Dayah Salafiyah method. (3) After the MoU in Helsinki, the situation in the Aceh Province began to improve, Islamic boarding schools began to be built. (4), the results of the education process for children victims of the Aceh conflict at the Ummul Ayman Islamic Boarding School after they leave or finish there are ustadz/teaching staff, establish study centers, writers, and continue